Dynamic and control analysis of modular multi-parallel rectifiers (MMR) - Zare, Firuz; Ghosh, A.; Davari, P.; Blaabjerg, F. (2017)
© 2017 IEEE. This paper presents dynamic analysis of a Modular Multi-Parallel Rectifier (MMR) based on state-space modelling. The proposed topology is suitable for high power motor drive or multi-parallel AC-DC applications, which can reduce line current harmonics emissions significantly. However, a proper controller is required to share and control current through each rectifier. Mathematical analysis and simulations have been carried out to verify the proposed controller under different operating conditions.